The Influence of Ethnicity on Electoral Decisions: A Study of Nigeria’s 2023 Presidential Election - Towoju, Adedoyin John; Asiyanbi, Kazeem Aderemi (NIU Journal of Humanities; Vol. 10 Núm. 1 (2025): NIU Journal of Humanities, Vol. 10 No. 1, March 2025, 2025)
Voting behavior in democracies has long been a subject of interest for political scientists, sociologists, and researchers. It not only determines the composition of governments but also reflects the political dynamics of a nation. In Nigeria, ethnicity has historically played a crucial role in shaping electoral choices, influencing democratic representation and political stability. This study examines the extent to which ethnicity influenced the voting behavior of the electorate during the 2023 Presidential Elections in Nigeria. A mixed-methods approach was adopted, combining both quantitative and qualitative research techniques. Data was collected through structured questionnaires and one-on-one interviews. The findings reveal that ethnicity significantly influenced voter decisions, with approximately 75% of respondents acknowledging its impact. Many interview participants highlighted the lack of comprehensive civic education as a major challenge, advocating for voter education programs that emphasize candidate qualifications over ethnic affiliations. This study contributes to the discourse on identity politics and democratic governance in Nigeria by highlighting the challenges posed by ethnic-driven voting patterns. To mitigate the negative effects of ethnic polarization in elections, the study recommends targeted civic education initiatives led by the Nigerian government, the National Orientation Agency (NOA), and educational institutions. Implementing a civic education curriculum that fosters national unity and encourages policy-driven electoral choices will be critical to strengthening Nigeria’s democratic process. Keywords: Voting, Election, & ethnicity